Clinical and Neuro-imaging Patterns of Meningiomas of Visual Pathway - Khalid Farooq, Muhammad Khalil, Tayyaba Gul Malik (Pakistan Journal of Ophthalmology, 2015)
Purpose: To highlight the clinical and neuro-imaging patterns of Meningiomas of visual pathway. Materials and Methods: It was a descriptive retrospective study conducted during 2007 to 2013. 94 patients with intra cranial Meningiomas affecting the visual pathway were selected for study. Clinical data included history, ocular and systemic examinations and neuro-imaging reports. Special attention was given to the neurological data, which was the only source available to us for diagnosing Meningiomas. Histological confirmation of Meningioma was available in 9.6% cases (n = 9). Results: Ninety – four patients, 51 females and 43 males (female: male ratio, 1.19:1) were included in the study. Mean age was 48.23 years. The commonest type of Meningioma affecting visual pathway was Meningioma of inner table of occipital bone causing mass effects on the occipital lobe (30.85%, n = 29). Other Meningiomas were Parasellar (21.3%, n = 20) and supra sellar Meningiomas (18.1%, n = 17) pressing upon optic chiasma. Tumor size ranged from 0.7 cm to 8.5 cm in smallest and largest dimensions respectively. Only one patient in our series had neurofibromatosis type 1 and one patient had neurofibromatosis type 2. Conclusion: Neuro-imaging including conventional radiology plays a pivotal role in non-interventional diagnosis of intracranial Meningiomas. Owing to the benign nature of Meningioma, it should be differentiated from other aggressive tumors which need to be diagnosed and treated at the earliest. Key words: Parasellar Meningiomas, Supra sellar Meningiomas, visual pathway, Dural tail sign, Neuro-imaging